2022
DOI: 10.3389/fgene.2022.793884
|View full text |Cite
|
Sign up to set email alerts
|

Immediate-Early, Early, and Late Responses to DNA Double Stranded Breaks

Abstract: Loss or rearrangement of genetic information can result from incorrect responses to DNA double strand breaks (DSBs). The cellular responses to DSBs encompass a range of highly coordinated events designed to detect and respond appropriately to the damage, thereby preserving genomic integrity. In analogy with events occurring during viral infection, we appropriate the terms Immediate-Early, Early, and Late to describe the pre-repair responses to DSBs. A distinguishing feature of the Immediate-Early response is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 276 publications
(395 reference statements)
1
50
0
Order By: Relevance
“…Of note, the E4F1 depletion did not impact on the formation of 53BP1 foci in response to Gemcitabine. The preservation of this marker of the early phase of the DNA damage-response, suggest that the early steps of this response, upstream of the ATM/ATR-CHK1 signaling, might still be functional in the E4F1-depleted cells ( Figure 6 ) [ 47 ].
Figure 5 E4F1-depletion impacts on ATM/ATR-CHK1 signaling in response to CT drugs Gemcitabine and Cisplatin.
…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the E4F1 depletion did not impact on the formation of 53BP1 foci in response to Gemcitabine. The preservation of this marker of the early phase of the DNA damage-response, suggest that the early steps of this response, upstream of the ATM/ATR-CHK1 signaling, might still be functional in the E4F1-depleted cells ( Figure 6 ) [ 47 ].
Figure 5 E4F1-depletion impacts on ATM/ATR-CHK1 signaling in response to CT drugs Gemcitabine and Cisplatin.
…”
Section: Resultsmentioning
confidence: 99%
“…Genome instability is a hallmark of cancer. The inappropriate responses to DNA damage or DNA repair disorders are linked to rearrangement of the genome, microsatellite instability, chromosome instability, and tumorigenesis [ 61 , 62 ]. We found that BORIS was ADP-ribosylated within 30 min after stimulation with single- and double-strand DNA, and BORIS facilitated the recruitment of Ku70.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated ATM phosphorylates H2AX, but DNA-dependent protein kinase catalytic subunit (DNA-PKcs), ataxia telangiectasia, and Rad3-related (ATR) also phosphorylate H2AX [ 15 , 16 , 17 ]. Additionally, increased levels of γH2AX on either side of the DSB further promote chromatin decondensation and DSB repair [ 18 ]. Chromatin structure is a key determinant of DSB repair pathway choice.…”
Section: Introductionmentioning
confidence: 99%